Utilisation and impact of the Merdeka Mengajar Platform in the implementation of the Merdeka curriculum: lessons from Guru Penggerak - Kusuma, Dewi Anggraini (Universitas Negeri Semarang, 2024)
Indonesia’s education system has transformed with implementing the Merdeka Curriculum, supported by PMM to enhance teaching effectiveness. While Guru Penggerak teachers actively use PMM, variations exist in their level of engagement. This study uses a qualitative evaluative approach with the STAKE model to examine the utilization of PMM among Guru Penggerak and its impact in schools. Data was collected through interviews, observations, and document analysis. Findings indicate that Guru Penggerak firmly understands PMM, which is supported by schools through dedicated teams and infrastructure. PMM utilisation aligns with guidelines, and key features are effectively implemented. The platform positively impacts teachers’ skills and self-development. However, time constraints due to additional administrative duties pose challenges. These findings highlight the benefits and barriers of PMM, offering insights for optimising its implementation to enhance educational outcomes.